Pursuing wellness
1 online resource (136 pages).
Keywords: First published in 2010 as a volume of Museums and Social Issues, A Journal of Reflective Discourse as Volume 5, number 2. What does wellness really mean? How do we enjoy the experience of being well or honor good health? What does it take to Pro-actively court the most positive potential for your future self? Health is one of the pressing topics of our age. This issue sets out to look at how museums create public value by bringing health issues to the fore.